Simple Plug‐In Synthetic Step for the Synthesis of (−)‐Camphor from Renewable Starting Materials. (15th June 2021) - Calderini, Elia; Drienovská, Ivana; Myrtollari, Kamela; Pressnig, Michaela; Sieber, Volker; Schwab, Helmut; Hofer, Michael; Kourist, Robert
Abstract: Racemic camphor and isoborneol are readily available as industrial side products, whereas (1 R )‐camphor is available from natural sources. Optically pure (1 S )‐camphor, however, is much more difficult to obtain. The synthesis of racemic camphor from α‐pinene proceeds via an intermediary racemic isobornyl ester, which is then hydrolyzed and oxidized to give camphor. We reasoned that enantioselective hydrolysis of isobornyl esters would give facile access to optically pure isoborneol and camphor isomers, respectively. While screening of a set of commercial lipases and esterases in the kinetic resolution of racemic monoterpenols did not lead to the identification of any enantioselective enzymes, the cephalosporin Esterase B from Burkholderia gladioli (EstB) and Esterase C (EstC) from Rhodococcus rhodochrous showed outstanding enantioselectivity (E>100) towards the butyryl esters of isoborneol, borneol and fenchol. The enantioselectivity was higher with increasing chain length of the acyl moiety of the substrate. The kinetic resolution of isobornyl butyrate can be easily integrated into the production of camphor from α‐pinene and thus allows the facile synthesis of optically pure monoterpenols from a renewable side‐product. Abstract : Enzymes are a valuable tool for upcycling side‐stream from renewable sources. We have found that EstB from Burkholderia gladioli could achieve high enantiopurity in upcycling α‐pinene, a side‐product from turpentine production, whereas common lipases and esterases could not. This reaction can be easily integrated with the existing chemical synthetic route for the production of the racemic camphor with minimal adjustments as the route goes through an intermediate isobornyl acetate.